2009
DOI: 10.1111/j.1600-0854.2009.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific Ubiquitination Determines Lysosomal Sorting and Signal Attenuation of the Granulocyte Colony‐Stimulating Factor Receptor

Abstract: Ubiquitination of cytokine receptors controls intracellular receptor routing and signal duration, but the underlying molecular determinants are unclear. The suppressor of cytokine signaling protein SOCS3 drives lysosomal degradation of the granulocyte colony-stimulating factor receptor (G-CSFR), depending on SOCS3-mediated ubiquitination of a specific lysine located in a conserved juxtamembrane motif. Here, we show that, despite ubiquitination of other lysines, positioning of a lysine within the membrane-proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…S3). By contrast, colocalization of the lysosomal routing defective G-CSFR mutant K5R persisted at 60 minutes after G-CSF stimulation, confirming that Prdx4 interacts with G-CSFR localized in early endosomes Wölfler et al, 2009) (supplementary material Fig. S4a).…”
Section: Colocalization Of Endocytosed G-csfr With Prdx4 Residing In mentioning
confidence: 66%
See 2 more Smart Citations
“…S3). By contrast, colocalization of the lysosomal routing defective G-CSFR mutant K5R persisted at 60 minutes after G-CSF stimulation, confirming that Prdx4 interacts with G-CSFR localized in early endosomes Wölfler et al, 2009) (supplementary material Fig. S4a).…”
Section: Colocalization Of Endocytosed G-csfr With Prdx4 Residing In mentioning
confidence: 66%
“…Intriguingly, the G-CSFR truncation mutants found in SCN and AML respond differentially to suppressor of cytokine signaling 3 (SOCS3) in terms of STAT3 versus STAT5 inhibition: SOCS3-mediated inhibition of STAT5 activation is abolished as a result of the G-CSFR truncation, whereas inhibition of STAT3 remained largely intact (van de Geijn et al, 2004). This discrepancy relates to the fact that SOCS3-induced STAT5 inhibition entirely depends on SOCS box-mediated ubiquitylation of G-CSFR, whereas SOCS3-induced STAT3 inhibition is less dependent on this process van de Geijn et al, 2004;Wölfler et al, 2009). Together with these previous results our current data suggest that, whereas attenuation of STAT5 mainly depends on lysosomal degradation of the activated G-CSFR, STAT3 inhibition is mediated mainly by dephosphorylation of STAT3-binding tyrosine motifs controlled by the kinase inhibitory region of SOCS3 and by Ptp1b, when the G-CSFR resides in the early endosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ES cells expressing endogenous levels of SOCS3 lacking the SOCS box express elevated levels of phosphorylated Jak1 in response to LIF (46). In contrast, a series of studies from Irandoust and coworkers demonstrated that SOCS3 ubiquitinates lysine residues on the G-CSF receptor cytoplasmic domain, facilitating its trafficking to the lysosome (47,48). Thus, while SOCS3 potentially regulates G-CSF and gp130 receptor signalling through the combination of its KIR and SH2 domain, the precise ubiquitination of the different proteins in these receptor complexes may provide an additional level of regulation.…”
Section: Sh2 Domain Socs Box Proteinsmentioning
confidence: 99%
“…It requires a three-step enzymatic cascade that transfers the small ubiquitin molecule from an E1-activating enzyme to an E2-conjugating enzyme, followed by the covalent attachment of ubiquitin to the e-amino group of a target lysine residue by an E3 ubiquitin ligase. Ubiquitin itself can be ubiquitinated on lysine, and at least eight distinct modifications have now been identified that include monoubiquitination, multimonoubiquitination and linear and branched polyubiquitination on one or more of the seven lysines found in ubiquitin (lysine 48 and lysine 63-linked polyubiquitination are the best characterised) (1). Increasingly, deregulation of the ubiquitination pathway components, including negative regulators such as deubiquitinating enzymes, is seen as having an important role in the aetiology of human diseases including cancer, autoimmunity and other chronic inflammatory diseases (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%